The Role Model of Islamic Religious Education Teachers as a Foundation for the Behavior of Learners in the Digital Age - Irawan, Andri; Mauzifa; Amali, Subhi; Fahmi, Hakim Ibnu; Rofiq, Hilman Muhammad (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2025)
This study aims to explore the importance of teachers, especially Islamic Religious Education teachers in maintaining their dignity in front of students because a teacher is a role model for them. The research methodology used used a combined method between qualitative and quantitative approaches. The findings of this study include: (1) Teachers are professional educators, not just teaching, but role models for students for academic qualifications at least Bachelor's degree and competencies at least pedagogic, professional, social and personality and for Islamic Religious Education teachers plus leadership and spiritual; (2) Teachers in the era of digitalization and artificial intelligence have an important role that cannot be replaced by anything because only teachers can inspire students; (3) Based on the findings in the field, exemplary teachers are in the total score range of 42.38, so the learners' perceptions of exemplary teachers can be categorized in the high category. This strengthens the assumption that Islamic religious education teachers have a central role in shaping students' behavior, both in the school environment and outside school.